Professional information and documentation at the Crossroads: competencies and professional profiles necessary to survive in a competitive environment - Tejada Artiga, Máster Carlos Miguel (2013)
It identifies different projects, both in Spain and internationally, that have identified professional profiles in Information Science. The limit of professions has become blurred and a competition emerges between them, to occupy spaces of action. So it requires a strengthening and diversification of our professional skills, developing new attitudes and changing our mindset, that constitute the specialization of our profiles.